Plaise a monseigneur le président avoir pour recommandé en justice le bon droit, pour Elie Bouhéreau, Elie Richard et Jean Seignette, médecins à La Rochelle, demandeurs, contre Jacques du Mont, Nicolas Venette et consors, médecins de la mesme ville, deffendeurs. - Bouhéreau, Élie, 1643-1719; Richard, Élie, 1645-1706; Seignette, Jean IV, 1654-1701. (s.l : s.n, 1683)
Appeal by Élie Bouhéreau, Jean Seignette and Élie Richard, against their exclusion from the college of Medicine in La Rochelle on the grounds that no edict or ordonnance had previously excluded members of the R.P.R from practicing medicine, which remained a free profession in La Rochelle.
Two copies.
Previously catalogued as: '2 copies of a pamphlet beginning "plaise a monseigneur le président avoir pour recommandé en justice le bon droit, pour Elie Bouhéreau, Elie Richard et Jean Seignette,médecins à La Rochelle, demandeurs, contre Jacques du Mont, Nicolas Venette et consors, médecins de la mesme ville, deffendeurs", [no date]
Copy 1: At the top of the first page in ink: '1684' struck through and 'Juillet 1683. Ce factum [...] l'advertissement appartenaient a Mr Bouhereau'
Request to his Lordship on behalf of Elie Bouhereau, Elie Richard, & Jean Seignette, Médecins à la Rochelle, Demandeurs: Contre jacques du Mont, Nicolas Venette, & Consors Médecins de la même Ville, Deffendeurs.
Signed by Monsieur Le Bouts, Rapporteur.
French